2017
DOI: 10.1074/jbc.m117.782300
|View full text |Cite
|
Sign up to set email alerts
|

Post-translational modifications clustering within proteolytic domains decrease mutant huntingtin toxicity

Abstract: Huntington's disease (HD) is caused in large part by a polyglutamine expansion within the huntingtin (Htt) protein. Post-translational modifications (PTMs) control and regulate many protein functions and cellular pathways, and PTMs of mutant Htt are likely important modulators of HD pathogenesis. Alterations of selected numbers of PTMs of Htt fragments have been shown to modulate Htt cellular localization and toxicity. In this study, we systematically introduced site-directed alterations in individual phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(73 citation statements)
references
References 54 publications
3
69
0
Order By: Relevance
“…Moreover, a recent study using a Drosophila model of HD expressing HTTex1 97Q via phosphomimetics showed that both S13D and S16D increase aggregation (Branco-Santos et al, 2017), in contrast to observations in mammalian cell models of HD showing that expression of the N-terminal fragments of HTT 1-171 142Q, HTTex1 97Q or HTTex1 82Q with S13D and S16D decreases mutant HTT-induced toxicity and aggregation (Arbez et al, 2017;Atwal et al, 2011;Branco-Santos et al, 2017). Although these findings show that PTMs, such as single or double phosphorylation, are sufficient to modify mutant HTT levels, aggregation, and toxicity, they highlight the limitations of using phosphomimetics.…”
mentioning
confidence: 81%
See 4 more Smart Citations
“…Moreover, a recent study using a Drosophila model of HD expressing HTTex1 97Q via phosphomimetics showed that both S13D and S16D increase aggregation (Branco-Santos et al, 2017), in contrast to observations in mammalian cell models of HD showing that expression of the N-terminal fragments of HTT 1-171 142Q, HTTex1 97Q or HTTex1 82Q with S13D and S16D decreases mutant HTT-induced toxicity and aggregation (Arbez et al, 2017;Atwal et al, 2011;Branco-Santos et al, 2017). Although these findings show that PTMs, such as single or double phosphorylation, are sufficient to modify mutant HTT levels, aggregation, and toxicity, they highlight the limitations of using phosphomimetics.…”
mentioning
confidence: 81%
“…HTT N17 domain was shown to contain a translocated promoter region (TPR)-dependent nuclear export signal (Atwal et al, 2007;Benn et al, 2005;Cornett et al, 2005;Maiuri et al, 2013;Rockabrand et al, 2007;Steffan et al, 2004). Mimicking phosphorylation at S13 and S16 (S13D/S16D) increased the localization of the HTT N17 peptide, HTTex1 or longer N-terminal HTT fragments to the nucleus (Arbez et al, 2017;Atwal et al, 2011;Havel et al, 2011;Thompson et al, 2009;Zheng et al, 2013). Moreover, we recently reported that single or double phosphorylation at S13 and/or S16 of HTTex1 significantly enhanced the targeting of mutant HTTex1 fibrils to the nuclear compartment (Deguire et al, 2018).…”
Section: Tbk1 Overexpression Affects Htt Subcellular Localization Andmentioning
confidence: 99%
See 3 more Smart Citations